LOS PROCESOS DE CODIFICACIÓN MÚLTIPLE EN EL DISCURSO ARTÍSTICO MUSICAL Y LITERARIO - González Martínez, Juan Miguel (Imafronte, 1999)
Vocal musical implies the convergence of music and verbal languaje to form a different semiotic and artistic unity. For this reason, the convenience of considering a single code as the support of all the mechanics which generate feelling in these types of discourse has been questioned. Furthermore, these discourse form a essentially hetereogenous really, considered as they are as expressive malter, wich participate in the inerent complexity of the artistic message. the consideration of the denotative and connotative processes, or the existence of different levels of meaning has led many authors to ponder on the presence of diverse processes of codification in the same discourse, literary, musical, or comunicative languaje. The co-existence or interaction of codes can serve to explain to multidimensionality of meaning charactaristics of vocal music and to overcome the limitations of the concept of code.